Keberagaman Hak dan Kewajiban Siswa dalam Membentuk Karakter - Yuda Pratiwi; Lukman Hakim; Nora Surmilasari (Journal on Education, 2023)
Citizenship Education is education that is closely related to shaping the character of students during the learning process at school. The research aims to identify and describe the role of Citizenship Education (PKn) in forming a characterful personality in elementary school children. The research method used is qualitative research. The data collection techniques in this study, namely through observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The object of this study is the role of Citizenship Education (Civics) in forming a characterful personality in elementary school children, namely fourth grade students at SD Negeri 1 Pulawan. There were 3 informants in the study, namely: Teachers as informants to find out the habits, traits, and character of students at school through interviews. The head of SD Negeri 1 Pulawan as an informant to find out whether Civics as a subject that shapes student character has been implemented well or not at school. Then students as parties who have information and provide data that are the subject of research to be observed during the Civics learning process and outside of school hours. The focus of research is the character of Discipline, Independence, and Responsibility. The results of this study indicate that Citizenship Education has an important role in building the character of students for the nation and the State to become better individuals. Citizenship Education in its teaching has a major impact on the character development of Elementary School students.